A RUN SUM S CHART WITH TWO SAMPLING INTERVALS - Lim, Alex Jun Xiong; Khoo, Michael Boon Chong; Yeong, Wai Chung; Haq, Abdul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
The variable sampling interval run sum (VSI RS) S chart that adopts two different sampling interval lengths on the run sum (RS) S chart is proposed. The Markov chain method is used to compute the optimal parameters that minimize the out-of-control zero state average time to signal (ATS), steady state ATS (SATS), expected ATS (EATS) and expected SATS (ESATS). The results show that the optimal VSI RS S chart outperforms the EWMA S chart in detecting moderate and large shifts while surpassing the RS S and standard S charts in detecting all sizes of shifts, in the process standard deviation. The ability of the VSI RS S chart to detect shifts in the process standard deviation quickly can improve productivity in manufacturing and reduce scrap and rework costs. An illustrative example is provided to facilitate the implementation of the proposed chart.